(untitled) (Stato, Chiese e pluralismo confessionale, 2019)
SOMMARIO: 1. La convocazione - 2. Le ragioni della convocazione - 3. La qualificazione del sinodo come “minore” - 4. Il tema del sinodo - 5. La commissione di coordinamento - 6. Il documento preparatorio - 7. Lo strumento di lavoro per i consigli diocesani - 8. I sinodali - 9. Le costituzioni -10. Valutazioni critiche. "Chiesa dalle genti", the minor synod of the diocese of Milan. Profiles of Canon law ABSTRACXT: In order to ensure a better pastoral care of foreigners the new archbishop of Milan has convened a minor synod. This form of ecclesial assembly is not contemplated by the Code of Canon Law, but has been practiced for centuries in the Ambrosian diocese. The archbishop renewed this tradition by inviting the diocesan presbyteral and pastoral councils to participate at the event. The decisions taken have had a significant impact on the life of the entire diocese, also as regards the territorial organization and the structure of the offices of the archiepiscopal curia. Overall, the synod can be considered exemplary in composition, procedure and efficiency, and hopefully will be imitated by other dioceses.